DEVELOPING REAL-LIFE ORIENTED KNOWLEDGE IN PHYSICS EDUCATION THROUGH PISA-STYLE TASKS - Mirzayeva , Umidakhon (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
This article highlights the pedagogical opportunities for developing real-life oriented practical knowledge and skills in physics education through the use of tasks from the Programme for International Student Assessment (PISA). It analyzes the content of PISA-style tasks, methods of their integration into the teaching process, and their role in fostering students’ functional literacy